Investigation of Plastic Ball Bearing Production by Additive Manufacturing - Agoren, Gorkem; Dogan, Burcu Kucukoglu; Karacay, Tuncay (Springer, 2025)
The aim of this study is to understand whether 3D-produced plastic bearings can replace those produced by plastic injection. First, bearings are produced with SLA and FDM and manufactured with these machines to determine which one is more suitable for bearing production. Then, four different resin types are developed for the inner and outer rings of 6205 polymer hybrid ball bearings with SLA. The findings showed that bearings produced with low elongation resins are not suitable for applications involving loads, as they are broken and fragmented during the tight-fit assembly. In addition, bearings produced with high-viscosity resins failed faster with increased wear and quantity of material during the operating period. These results show that manufacturing and material constraints increase when applying SLA to loading solutions. Nonetheless, the study shows that additive manufacturing has the possibility of specialized, low-volume bearing applications where complicated geometries and quick prototyping are required, provided that resin selection and process modifications are addressed.
Keywords: additive manufacturing; production of plastic ball bearing; SLA